2021
DOI: 10.1128/jcm.02277-20
|View full text |Cite
|
Sign up to set email alerts
|

Inference of Active Viral Replication in Cases with Sustained Positive Reverse Transcription-PCR Results for SARS-CoV-2

Abstract: Objectives: The purpose of this study was to detect COVID-19 cases with persistent positive RT-PCR results for SARS-CoV-2, for which viable virus can be inferred, due to the presence of subgenomic (SG) viral RNA, which is expressed only in replicating viruses. Methods: RNA remnants, purified from diagnostic nasopharyngeal specimens, were used as templates for RT-PCR specific detection of SG E gene RNA. As controls, we also detected viral genomic RNA for the E gene and/or a human housekeeping gene (RNase P). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 14 publications
1
44
0
Order By: Relevance
“…Relatively, smaller cohorts of 23 and 33 patients from Hong Kong and China recorded viral shedding for a maximum of 25 and 59 days, respectively [15, 16]. An Italian study reported the maximum days of viral shedding to be 101 in a cohort of 60 patients [17].…”
Section: Resultsmentioning
confidence: 99%
“…Relatively, smaller cohorts of 23 and 33 patients from Hong Kong and China recorded viral shedding for a maximum of 25 and 59 days, respectively [15, 16]. An Italian study reported the maximum days of viral shedding to be 101 in a cohort of 60 patients [17].…”
Section: Resultsmentioning
confidence: 99%
“…It should be recalled that SARS-CoV-2 virions do not contain subgenomic RNA—i.e., RNA replicative forms thought to encode the structural spike (S), E, membrane (M), or N virus proteins—whereas subgenomic RNA is part of cellular membrane vesicles and thereby relatively stable (15). Thus, antigen and subgenomic RNA represent two virus biology entities worthy of investigation in clinical samples (7, 18, 19), especially in situations of prolonged (genomic RNA) RT-PCR positivity implying infectious virus shedding (15).…”
Section: Discussionmentioning
confidence: 99%
“…Based on viral culture, the percent of these individuals who remain infectious approaches zero by 10‐15 days after the onset of symptoms 47‐49 . However, shedding of infectious SARS‐CoV‐2 has been demonstrated by viral culture or inferred by the presence of subgenomic RNA in a subset of individuals, including immunosuppressed hosts, for months following infection 50,51 . Higher Cq values of SARS‐CoV‐2 RT‐PCR reflect lower viral loads, and multiple studies have demonstrated inability to culture infectious virus above certain Cq thresholds 48 .…”
Section: Discussionmentioning
confidence: 99%